Following Islamic reality show personalities on twitter: a uses and gratification approach to understanding parasocial interaction and social media use - Tengku Mohd Azzman, Tengku Siti Aisha; Shariffadeen, Mohd Azzman; A.Manaf, Aini Maznina (IIUM Press, 2017)
Islamic reality shows started in Malaysia with Imam Muda, produced in 2010 by Astro Oasis. Since then, other television stations in Malaysia have also adopted this format. Using uses and gratification as a theoretical framework, a major focus of this paper was to examine the effects of Islamic reality shows on its audience, specifically on the parasocial relationships formed between Twitter users and their favorite Islamic reality show personality. It was predicted that active social media users would be more inclined to watch Islamic reality shows because of specific Twitter habits related to the show, and level of religiosity. A survey was conducted among students taking introductory Human Sciences and Islamic Revealed Knowledge subjects from the International Islamic University of Malaysia (IIUM). Among others, evidence from this research suggests that being relatable to viewers is important for mediated characters. Specifically, the level of parasocial interaction was found to significantly influence motivation to use Twitter, and intention to watch Islamic reality shows in the future, because of their Twitter use. However, religiosity did not influence intention to watch Islamic reality shows. The implications of these findings on the role of parasocial interaction, and the effects of social media on television viewing were discussed in this paper.